Mn2+‐Doped Metal Halide Perovskites: Structure, Photoluminescence, and Application. Issue 1 (30th November 2020) - Su, Binbin; Zhou, Guojun; Huang, Jinglong; Song, Enhai; Nag, Angshuman; Xia, Zhiguo
Abstract: Doping impurity ions into semiconductor luminescent materials offers a unique pathway for inducing new emission centers and enabling photoluminescence (PL) tuning. Among various luminescence materials, doping Mn 2+ into metal halide perovskites becomes a hot topic since Mn 2+ ions demonstrate an energy transfer route from host to dopants, resulting in interesting photophysical properties. This review aims to discuss the PL properties of Mn 2+ ions in halide perovskites nanocrystals or bulk crystals with different structural dimensions and local environments (MnX4 2– tetrahedron, MnX6 2– octahedron, or shortest Mn─Mn distance). In this regard, the effects of Mn 2+ doping on the PL properties and their modifications are summarized. Variable ion exchange dynamics, increased emission intensity, and enhanced stability induced by Mn 2+ doping are analyzed. These results also provide beneficial insights into applications of the doped luminescent halide perovskites. Finally, the present challenges in Mn 2+ ‐doped luminescent halide perovskites are elaborated. Abstract : Doping Mn 2+ into metal halide perovskites offers a unique pathway for inducing new emission centers and enabling photoluminescence (PL) tuning. PL mechanisms, properties, and their modification strategies of Mn 2+ ions in halide perovskites with different structural dimensions and local environments are discussed, and their applications are also summarized.